Legal Protection and Rights of Children Born of Rape: Islamic and Indonesian Legal Perspectives - Innike Putri Artha; Widiya Yul (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Children born as a result of rape occupy a complex legal position involving issues of lineage, guardianship, inheritance, identity, and legal protection. While Indonesian Child Protection Law guarantees equal rights for all children without discrimination, Islamic Family Law imposes specific legal consequences related to lineage (nasab) and family relations. Despite increasing scholarship on children born outside marriage, comparative studies examining the status and rights of children born of rape from both legal perspectives remain limited. This study aims to analyze and compare the legal status, rights, and protection mechanisms afforded to children born of rape under Islamic Family Law and Indonesian Child Protection Law. Employing a normative juridical approach, the research uses a comparative legal analysis based on the Qur’an, Hadith, the Compilation of Islamic Law, Law Number 35 of 2014, Constitutional Court Decision Number 46/PUU-VIII/2010, and relevant legal literature. The findings indicate that Islamic Family Law limits legal affiliation to the maternal lineage, affecting guardianship and inheritance rights, whereas Indonesian Child Protection Law adopts a rights-based approach emphasizing equality, identity rights, and broader legal protection. The study identifies a normative tension between lineage preservation and child-rights protection and proposes a maqāṣid al-sharī‘ah oriented, child-centered framework to strengthen legal protection for children born of rape in Indonesia.